Dampak Asas Erga Omnes dalam Putusan Mahkamah Konstitusi: Studi tentang Batasan Legal Standing dalam Pengajuan Permohonan Pengujian Undang-Undang di Mahkamah Konstitusi - Cornelia Angelica; Simplexius Asa; Rizal Thene (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The Constitutional Court's decision not only affects individuals or certain groups, but also has significant consequences for the public and the country as a whole. The Constitutional Court's decision provides legal certainty for society and the government by determining the implementation or cancellation of a policy that can help create a stable and predictable legal environment. This research is a normative research by studying and basing it on secondary data. Then analyzed using qualitative analysis. The results of this study indicate that the interests recognized by law in Indonesia regarding legal standing still revolve around proving real losses as a form of interest recognized by the Constitution. The principle of erga omnes has an important meaning in the Constitutional Court's decision. An appropriate alternative is needed to ensure that the decision that then has an impact on everyone does not result in new constitutional losses for parties who are not in dispute. the implementation of the Constitutional Court's decision still faces serious challenges, ranging from delays in implementation to ignoring the decision by related institution.